2007
DOI: 10.1002/pon.1078
|View full text |Cite
|
Sign up to set email alerts
|

Cancer support groups: a critical review of empirical studies

Abstract: Support groups for adults affected by cancer are widely offered by local community and national agencies in North America. This type of psychosocial intervention is defined in terms of its structure and functions, and its theoretical underpinnings and models of practice are described. Forty-four empirical studies of professionally led cancer support groups are summarized and critically reviewed. These studies include 32 outcome evaluations of randomized controlled trials, two process evaluations, and 10 consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
120
0
7

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(137 citation statements)
references
References 82 publications
9
120
0
7
Order By: Relevance
“…While acknowledging that their study was small (n=63), Pruthi et al, (2009) pointed to the likelihood that massage may help patients with breast cancer to relax and feel better overall. Similar to our study, Gottlieb & Wachala (2007) observed high levels of consumer satisfaction in their critical review of 44 studies of professionally led cancer support groups. This level of satisfaction may be related to feeling happier and more at ease, receiving practical and emotional support and experiencing a sense of comfort and camaraderie (Hoey et al, 2008).…”
Section: Discussionsupporting
confidence: 73%
“…While acknowledging that their study was small (n=63), Pruthi et al, (2009) pointed to the likelihood that massage may help patients with breast cancer to relax and feel better overall. Similar to our study, Gottlieb & Wachala (2007) observed high levels of consumer satisfaction in their critical review of 44 studies of professionally led cancer support groups. This level of satisfaction may be related to feeling happier and more at ease, receiving practical and emotional support and experiencing a sense of comfort and camaraderie (Hoey et al, 2008).…”
Section: Discussionsupporting
confidence: 73%
“…For example, peer support has been found to be effective in increasing breast-feeding duration; improving self-efficacy and well-being in individuals with heart disease; improving fitness, strength, and sport competence for breast cancer survivors; enhancing mental health; and increasing chronic disease management and health-related quality of life [27][28][29][30]. Additionally, peer support is especially vital and influential to adolescents, as they spend increased time with peers, enhancing the potential for the norms and behaviours of peers to influence them [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Our goal was to leverage their expertise in providing support, to better understand the role of online support, including how it compares to face-to-face support, and whether it could complement traditional supportive care services. Hence, the study purpose was twofold: (1) to identify the extent to which this unique sample of breast cancer survivors used online communities including their timing, frequency and reasons for use; and (2) to explore the conditions under which they used online communities, and how they compare to traditional sources of supportive care. Lastly, as the results were being analyzed it became apparent that theories of social support, technology adoption and health behavior could help to explain the study findings.…”
mentioning
confidence: 99%